Palatal Obturator after Maxillectomy following Squamous Cell Carcinoma - Karim Chebbi; Khaoula Bouaziz; Oumaima Tayari; Azza Berkaoui; Mohamed Ali Bouzidi; Jamila Jaouadi (Hindawi Limited, 2022)
After surgical excision of tumors involving the maxilla, depending on their location and size, maxillary defects can have harmful consequences, both esthetic and functional. These effects disrupt all the functions of the manducatory system, namely breathing, swallowing, and especially phonation, thus affecting negatively the patient's psychological state. Despite the evolution of reconstructive surgical techniques and the development of microsurgery, conventional obturator prostheses are still relevant. In fact, these prostheses restore the main functions of chewing, phonation, and swallowing. They also provide the patient with a satisfactory esthetic appearance. Moreover, they have an advantage in regard to oncology, making the possibility of surveying much easier. Maxillary defects are characterized by their highly polymorphic aspect, having a great impact on the nature of prosthetic rehabilitation. The aim of this work was to present the different clinical and laboratory steps of prosthetic rehabilitation of an acquired maxillary defect following excision of a mucoepidermoid carcinoma.